3D porous flower-like CoAl2O4 to boost the photocatalytic CO2 reduction reaction. Issue 6 (18th January 2023) - Lv, Fei; Zhang, Wenyuan; He, Lang; Bai, Xue; Song, Yi; Zhao, Yan
Abstract : The conversion efficiency and stability of photocatalysts play important roles in the full photocatalytic CO2 reduction cycle. Abstract : The conversion efficiency and stability of photocatalysts play important roles in the full photocatalytic CO2 reduction cycle. In this work, a simple hydrothermal and thermal treatment method was used to convert thin 3D flower-like CoAl-layered double hydroxides (CoAl-LDHs) into ultrathin flower-like 3D porous spinel CoAl2 O4 (CoAl). The yields of the optimized CoAl-750 catalyst for CH4 and CO after 7 h of illumination were 58.98 μmol g −1 and 33.11 μmol g −1, respectively. The CoAl-750 catalyst demonstrates high stability after 35 h of cycling, with the yields of CH4 and CO being 107.19% and 98.38% of those in the first cycle, respectively. The CoAl spinel catalysts exhibit outstanding stability, while increasing the conversion efficiency of photocatalytic CO2 reduction. The excellent catalytic performance is attributed to the ultra-thin porous 2D nanosheets and spinel structure of CoAl. This work is expected to open new avenues for the application of spinel CoAl2 O4 in photocatalysis.